2018
DOI: 10.21307/ane-2018-027
|View full text |Cite
|
Sign up to set email alerts
|

c-Fos and neuronal plasticity: the aftermath of Kaczmarek’s theory

Abstract: The development of molecular biology methods in the early 1980s led to a better understanding of the role of transcription factors in mammalian cells. The discovery that some transcription factors are critically important for cells to switch between different functional states was fundamental for modern molecular neurobiology. In the 1980s Leszek Kaczmarek proposed that, analogically to the cell cycle or to cell differentiation, long-term synaptic plasticity, learning, and memory should also require the activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 109 publications
(119 reference statements)
1
31
1
Order By: Relevance
“…Several reports demonstrated that E4 orf6 enhances the oncogenic effect of adenovirus E1A and E1B [12] [13]. As shown in Figure 4E, the numbers of transformed colonies that were transformed by E1 and HuB were significantly higher compared with E1-HuR [19]. It has been also reported that histon acetyltransferase (HAT) activity of CREBBP (CREB-binding protein), another ARE mRNA, is involved in memory consolidation [20].…”
Section: Discussionmentioning
confidence: 78%
“…Several reports demonstrated that E4 orf6 enhances the oncogenic effect of adenovirus E1A and E1B [12] [13]. As shown in Figure 4E, the numbers of transformed colonies that were transformed by E1 and HuB were significantly higher compared with E1-HuR [19]. It has been also reported that histon acetyltransferase (HAT) activity of CREBBP (CREB-binding protein), another ARE mRNA, is involved in memory consolidation [20].…”
Section: Discussionmentioning
confidence: 78%
“…2A). As we could not record EPSPs and spikes in the incubator we used the immediate early gene cFos that is upregulated in burst-spiking neurons (Schoenenberger, Gerosa and Oertner, 2009) and in neurons that have undergone LTP (for review see Jaworski, Kalita and Knapska, 2018) as a surrogate. We found no cFos-positive ChrimsonR-CA3 neurons after causal pairing (9/9 slices) indicating that these neurons were not driven to burst by either the 630 nm light flashes (300 at 5 Hz, 8 mW mm −2 ) or the 405 nm flashes (300 bursts of 3 at 50 Hz, 12 ms delay, 1 mW mm −2 ).…”
Section: Resultsmentioning
confidence: 99%
“…FOS gene is expressed in almost every tissue (https://www .ncbi.nlm.nih.gov/gene/2353). One of the most thorough research of this gene is focused on neuronal plasticity [51,52]. Animal models of anxiety, fear, and depression show increased FOS in the brain areas linked to the formation of these behavioral reactions in animals [53][54][55].…”
Section: Fosmentioning
confidence: 99%